2009
DOI: 10.1152/ajpheart.01045.2008
|View full text |Cite
|
Sign up to set email alerts
|

Lateralization of expression of neural sympathetic activity to the vessels and effects of carotid baroreceptor stimulation

Abstract: Furlan R. Lateralization of expression of neural sympathetic activity to the vessels and effects of carotid baroreceptor stimulation. Am J Physiol Heart Circ Physiol 296: H1758 -H1765, 2009. First published April 10, 2009 doi:10.1152/ajpheart.01045.2008.-Human studies suggest that cardiovascular neural sympathetic control is predominantly modulated by the right cerebral hemisphere. It is unknown whether post-ganglionic sympathetic activity [muscle sympathetic nerve activity (MSNA)] shows any functional asymme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 31 publications
(30 reference statements)
1
55
0
Order By: Relevance
“…Moreover, the response appears to be variable and some patients may not respond stimulation exhibited better blood pressure control compared with patients with unilateral left-sided stimulation. This observation would support the idea that baroreflex regulation is asymmetric as suggested based on human physiological experiments using neck suction [31][32][33]. However, all these findings have to be interpreted with great caution because comparisons between stimulation settings were not conducted in a systematical fashion.…”
Section: Efficacy Of Electrical Carotid Sinus Stimulation In Loweringsupporting
confidence: 79%
“…Moreover, the response appears to be variable and some patients may not respond stimulation exhibited better blood pressure control compared with patients with unilateral left-sided stimulation. This observation would support the idea that baroreflex regulation is asymmetric as suggested based on human physiological experiments using neck suction [31][32][33]. However, all these findings have to be interpreted with great caution because comparisons between stimulation settings were not conducted in a systematical fashion.…”
Section: Efficacy Of Electrical Carotid Sinus Stimulation In Loweringsupporting
confidence: 79%
“…Because sinusoidal baroreflex activation is able to abolish the difference, the data also suggest that this is a functional rather than an anatomically related phenomenon. 8 In a study on 12 volunteers, Furlan et al 9 also found greater effects of neck suction on the right side than on the left one. All these studies, however, focused on changes in heart rate and blood pressure variability and not on blood pressure alterations per se.…”
Section: Discussionmentioning
confidence: 94%
“…Further observations indicated that during spontaneous breathing there is a rightsided predominance in strength of muscle sympathetic activity at rest but that this right-left difference disappears during carotid baroreflex stimulation, regardless of whether unilateral or bilateral stimulation is applied. 8 In other words, it seems that sympathetic activity at rest is stronger in the right part of the body. Because sinusoidal baroreflex activation is able to abolish the difference, the data also suggest that this is a functional rather than an anatomically related phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are consistent with animal studies indicating right-sided predominance of the carotid baroreflex; 93 studies in humans using the neck suction device are inconclusive. [94][95][96] Future trials of carotid baroreflex activation therapy for resistant hypertension should be designed to overcome the limitations of this first phase III trial. Meanwhile, a s econd-generation miniaturized device-Barostim neo™-for unilateral pacing has been designed to reduce surgical procedure time and facial nerve complications and to improve efficacy.…”
Section: Phase III Trialsmentioning
confidence: 99%